Organizational Innovativeness Among SMEs in Malaysia Halal Industry - Mazita, Mokhtar; Noor Azlinna, Azizan; Ida Rizyani, Tahir; Shariman, Mustafa (2014)
Achievement in today’s dynamic business environment requires innovation as it is said to be one of the most important factors in economic competition. It is also been considered as a fundamental organizational competency to sustain in the long run as suggested by Khalifa, Yu, & Shen (2007). Meanwhile Hult, Hurley, & Knight (2004) proposed that innovativeness is a key factor for competitive advantage towards superior performance. This growing recognition has created a sense of interest among the scholars to discover methods and factors that influence innovativeness in the organization. Innovativeness is thought to be an antecedent of organizational performance (Hurley & Hult, 1998) but what drives innovativeness and key drivers is still under explored (Hult, et al., 2004).